2016
DOI: 10.1055/s-0036-1584017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Clarithromycin-Resistant Helicobacter pylori Strains in Gastric Mucosa-Associated Lymphoid Tissue Lymphoma Patients

Abstract: Gastric MALT lymphoma is closely associated with Helicobacter pylori infection. Bacterial eradication therapy comprising clarithromycin is the first-line treatment in gastric MALT lymphoma patients. However, antimicrobial resistance to clarithromycin has been increasing in Europe, and thus far, it has not been examined in gastric MALT lymphoma patients. Based upon histopathological investigation, 17 adult gastric MALT lymphoma patients were identified to be related with H. pylori infection between 1997 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…While initially having been included in most regimens applied for eradication of HP, the increasing rate of resistance to clarithromycin of various HP strains is becoming a problem. While a small study in Austria has shown the rate of clarithromycin-resistant HP strains to be roughly 13% in MALT lymphoma patients, 7 the small number of patients studied along with the fact that the overall resistance rate is among the highest in Europe has led to the recommendation that clarithromycin should no longer be used in a triplet HP-eradication therapy, while it is still recommended as part of quadruple therapies according to the Maastricht V consensus. 8,9 Emerging results have shown a surprisingly high direct antineoplastic activity of the macrolide in patients with MALT lymphoma, including heavily pretreated patients.…”
Section: Introductionmentioning
confidence: 99%
“…While initially having been included in most regimens applied for eradication of HP, the increasing rate of resistance to clarithromycin of various HP strains is becoming a problem. While a small study in Austria has shown the rate of clarithromycin-resistant HP strains to be roughly 13% in MALT lymphoma patients, 7 the small number of patients studied along with the fact that the overall resistance rate is among the highest in Europe has led to the recommendation that clarithromycin should no longer be used in a triplet HP-eradication therapy, while it is still recommended as part of quadruple therapies according to the Maastricht V consensus. 8,9 Emerging results have shown a surprisingly high direct antineoplastic activity of the macrolide in patients with MALT lymphoma, including heavily pretreated patients.…”
Section: Introductionmentioning
confidence: 99%